Specific warm-up exercise is the best for vertical countermovement jump in young volleyball players - Fernando Nazário de Rezende; Gustavo Ribeiro da Mota; Charles Ricardo Lopes; Bruno Victor C. da Silva; Mário A. M. Simim; Moacir Marocolo
Abstract We evaluated the effect of performing various distinct warm-up exercises on vertical countermovement jump (VCMJ) performance. Eight volleyball players (age 15.4 ± 0.5 yrs) performed five different warm-up activities (in a counterbalanced, randomized crossover study) over five days, at 24-h intervals: stretching (4 × 30 s, 30 s between sets), cycloergometer (5 min at 50 W + 5 min at 100 W), resistance exercise (leg press 45°, 3 × 5 repetitions maximum, 3-min pause between sets), specific vertical jumping (4 × 10 VCMJ, 2-min pause between sets), and no warm-up at all (control condition). Beginning 3 min after their warm-up, the players performed 3 attempts (at intervals of 3 min) of VCMJ (on a contact carpet), and each player's best jump was considered in the analysis. All warm-up activities presented higher VCMJ performance (p< 0.05) than the control condition, with the exception of stretching. Vertical jumping revealed a large effect size(0.8) than other interventions. We conclude that in practical terms, vertical jumps are the best warm-up exercise (when applied by itself) to acutely improve VCMJ performance in volleyball players, but that other exercises can make a complementary contribution.